DEKONSTRUKSI DONGENG CINDERELLA DALAM CERPEN â€œPEREMPUAN BUTA TANPA IBU JARIâ€ KARYA INTAN PARAMADITHA - Megasari, Firenda Dian (Jurnal Pena Indonesia, 2019)
This research aims to describe about deconstruction of Cinderella tale in Intan Paramadithaâ€™s shortstory â€œPerempuan Buta tanpa Ibu Jariâ€. The theory used in this research is Derridaâ€™s deconstruction by using the concept of metaphysical binary oposition to find and identify contradictions inside the text. The result of this research shows that a work can be intended more than one way based on many point of views. Same like in this research that the one who become antagonist can changed into protagonist by seeing of many chances that presented by the author.